Examining school-aged youth - Adimando, Andrea (Legal Resources for School Health Services, 2017)
A comprehensive resource that addresses the legal issues regarding school health services for school nurses, school administrators and school attorneys. Over 50 topics are included including information on federal laws, compliance, medication administration, professional licensure and malpractice, minor rights and mental health and much more. Over 70 authors include school nurse experts, and education and nurse attorneys. Each chapter is evidence based and peer reviewed by both school nurse content experts and attorneys. Responds to questions submitted by school nurses and school administrators. A reference that will support school nurse and school health practice, enhance care to children and provide guidance to protect the school and school nurse.
Keywords: dept.nur

School nurse guidelines for: Developmental disabilities - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Enuresis - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Fractures - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: skin and soft tissue infection (Boils, Cellulitis, Lymphangitis, and MRSA) - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Cardiac conditions - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Human Papillomavirus (HPV) - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Mosquito-borne disease - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Puncture wounds - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Abrasions - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Allergies - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Bipolar disorders - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

School nurse guidelines for: Depression - Towle, Antoinette (Legal resource for school health services, 2020)
Keywords: dept.nur

The process for delegation in the school setting - Resha, Cheryl Ann (Legal Resources for School Health Services, 2017)
A comprehensive resource that addresses the legal issues regarding school health services for school nurses, school administrators and school attorneys. Over 50 topics are included including information on federal laws, compliance, medication administration, professional licensure and malpractice, minor rights and mental health and much more. Over 70 authors include school nurse experts, and education and nurse attorneys. Each chapter is evidence based and peer reviewed by both school nurse content experts and attorneys. Responds to questions submitted by school nurses and school administrators. A reference that will support school nurse and school health practice, enhance care to children and provide guidance to protect the school and school nurse.
Keywords: dept.nur